Effect of temperature on capping efficiency of zeolite and activated carbon under fabric mats for interrupting nutrient release from sediments - Hong, Seung Hee; Lee, Jae In; Lee, Chang Gu; Park, Seong Jik (Scientific Reports, 2019)
We investigated the influence of temperature on the capping efficiency to interrupt the release of nutrients from lake sediments. A 3-cm layer of Zeolite (ZL) or activated carbon (AC) was placed on the contaminated sediments, and nonwoven fabric mats (NWFM) were placed on top of these capping materials. Laboratory incubation experiments were performed under three different temperatures, namely 4, 15, and 30 °C. Under the uncapped condition at 30 °C, dissolved oxygen (DO) was depleted after 30 days, while at 4 °C and 15 °C, DO was present until the end of this experiment. DO concentration in overlying water was more dependent on the temperature than capping condition. ZL/NWFM effectively blocked the release of N from the sediments, and the capping efficiencies of ZL/NWFM for NH4-N at 4, 15, and 30 °C were 98%, 96%, and 94%, respectively. For the interruption of P release, both ZL/NWFM and AC/NWFM were not effective at 4 and 15 °C. At 30 °C, however, AC/NWFM was effective, and its capping efficiencies at 30 °C for PO4-P and T-P were 74.0% and 79.9%, respectively. In summary, nutrient release from sediments was accelerated at higher temperatures, and the effect of capping was significant at high temperature.